MIMOSA PUDICA-LOADED NANOEMUGEL: A PROMISING TOPICAL SYSTEM FOR SKIN CANCER MANAGEMENT - VAISHALI GAIKWAD; RAVINDRA LAWARE; NITIN MOHIRE; SOMNATH BHINGE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The skin, being the body’s largest organ, functions as a vital protective barrier but is highly vulnerable to environmental challenges, including chemical mutagens and carcinogens encountered daily. This study focuses on the development and characterization of Mimosa pudica-loaded PLAROsomes nanoemugel for enhanced therapeutic efficacy against skin cancer. Methods: A nanoemugel containing M. pudica extract (2.5% w/w) and Carbopol Ultrez 10 NF (2.5% w/w) using a modified formulation approach. The objective was to enhance the solubility, permeation, and therapeutic efficacy of M. pudica for treating skin cancer. The formulation incorporated rose oil and oleic acid, combined with Tween 20 and propylene glycol as a Smix system. Comprehensive evaluation of the nanoemugel was conducted, including in vitro drug release, viscosity assessment, thermal and morphological analyses (scanning electron microscopy and transmission electron microscopy [TEM]), globule size distribution, zeta potential measurement, in vitro cytotoxicity through the MTT assay. Results: The thermal analysis of the formulation revealed its thermal stability and highlighted potential interactions between the M. pudica extract and the PLARosomal matrix. The nanoemugel demonstrated a globule size of 122.9 nm, with TEM analysis confirming particle agglomeration and circular morphology, measuring 82.3±12 nm. A sustained drug release profile was observed, with cumulative release reaching 68.25% over 48 h. Stability studies confirmed the formulation’s robustness under storage conditions. In vitro cytotoxicity assays on cancer cells showed enhanced efficacy, with a cell viability percentage of 50.21% at a concentration of 100 μg mL-1. Conclusion: These findings indicate that M. pudica-loaded PLAROsomes nanoemugel is a promising candidate for targeted topical therapy in skin cancer treatment.